2019
DOI: 10.29359/bjhpa.2019.suppl.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Consumer loyalty among fans of sports clubs: How much do they vary across disciplines?

Abstract: Background: In the sports sector, the expected outcome of having loyal fans is equated with the amount and frequency of game attendance, the purchase of team merchandise, following the club's results in the media, and participation in discussions about the club, whereas the level of loyalty is determined by team identification and customer satisfaction with the team's performance. However, previous studies have not investigated the differentiation of the loyalty of club fans across different sports disciplines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…Purchasing a favorite football club's related products was one of the most important behavioral factors (Martin, 2013). It is also found that the football fans have the highest level of identification and they consume more club's products than the other sports fans such as volleyball (Kościołek, 2019). In this study, the findings show that the majority of the fans who participated in the study have purchased products related to their football club with a percentage of 53.3% and 12.2% answered that it is their duty as a fan of the team to purchase these products.…”
Section: Loyal Fans As Consumersmentioning
confidence: 59%
“…Purchasing a favorite football club's related products was one of the most important behavioral factors (Martin, 2013). It is also found that the football fans have the highest level of identification and they consume more club's products than the other sports fans such as volleyball (Kościołek, 2019). In this study, the findings show that the majority of the fans who participated in the study have purchased products related to their football club with a percentage of 53.3% and 12.2% answered that it is their duty as a fan of the team to purchase these products.…”
Section: Loyal Fans As Consumersmentioning
confidence: 59%
“…A literatura aponta que há preditores importantíssimos para que o adepto tenha intenções comportamentais favoráveis. Por exemplo, a satisfação em relação aos serviços e aos produtos oferecidos e a identificação com a organização desportiva são os preditores mais identificados (Biscaia, Correia, Rosado, Maroco & Ross, 2012;eodorakis, Alexandris, Tsigilis & Karvounis, 2013;Biscaia, Correia, Yoshida, Rosado & Marôco, 2013;Rodrigues, Sousa & Fagundes, 2018;Kościołek, 2019;Worastcheck, Horbel & Popp, 2019). Esses dois preditores, além de forte influência direta, também tem forte influência ao exercer um papel de moderador (indireto) entre duas dimensões (sendo as intenções comportamentais favoráveis como desfecho).…”
Section: Tabela 7 Resultado Dos Valores Percentuais Do Exp (βI)unclassified
“…The loyalty attitudes among supporters of sports teams indicate behavioural results in terms of the quantity and frequency of game attendance, watching the club's games on television, donning the club's colours and logo, and participating in debates about the team. Customer satisfaction and team identification are the two most crucial loyalty attitudes underlie loyalty actions (Kościółek, 2019).…”
Section: Loyaltymentioning
confidence: 99%
“…Continually belonging to the same sports club for an extended time, expanding the size and breadth of membership, or recommending the club to others are all examples of loyalty in a sporting field. Additionally, behaviorally loyal consumers are less likely to transfer memberships even if a subscription is cheaper elsewhere since they are more inclined to complain about problems rather than changing service providers (Kościółek, 2019). Schijns et al, (2016) argued that an emotional bond with the sports team (also known as "my club"), a sense of duty to remain a member, and the perception that there are not many other clubs to switch to are all components of attitude loyalty.…”
Section: Loyaltymentioning
confidence: 99%